Biomarcadores sanguíneos de exposição à zearalenona e aplicabilidade na avaliação da eficiência de aditivos antimicotoxinas em suínos e bovinos - Tonini, Camila (2020)
The inclusion of antimycotoxins additives (AMA) in the diet of production animals has been used to avoid mycotoxins exposure. To confirm the efficacy of such products in vivo, measurement of mycotoxins and/or their metabolites in biological fluids is preconized. This work consists of two studies and aimed to: (a) improve an analytical methodology based on High Performance Liquid Chromatography Coupled to Tandem Mass Spectrometry (HPLC-MS/MS) to detect and quantify zearalenone (ZEA) and its metabolites, α-zearalenol (α-ZOL), β-zearalenol, α-zearalanol, β-zearalanol (β-ZAL) and zearalanone, in blood serum; and (b) to conduct tests in species which are susceptible to ZEA to evaluate exposure to mycotoxicosis and to use serological biomarkers to assess the efficacy of AMA. In the first study, 24 beef heifers were randomly assigned to receive one of these treatments (n=6/treatament): T1) basal diet (control); T2) basal diet + 5 mg/kg ZEA; T3) basal diet + 5 mg/kg ZEA + 2.5 kg/t AMA; and T4) basal diet + 5 mg/kg ZEA + 5.0 kg/t AMA. The trial lasted 37 days. Blood was collected on different days after the diet was given, and the samples were centrifuged to obtain the blood serum and then analysed by HPLC-MS/MS. Among the analyzed metabolliates, β-ZAL was detected above the limit of quantification both in the unconjugated (>0.60 μg/kg) and conjugated (>1.70 μg/kg) forms. The remaining metabolites presented concentrations under the limit of detection. In the efficacy evaluation of the AMA, there was no significant difference (P>0.05) between the treatments with and without AMA at the tested levels of inclusion. In the second study, 70 pre-pubertal gilts were distributed in seven feeding groups (n=10/treatment) receiving diets with two levels of three clay-based AMAs (0.25% and 0.50%) and three levels of ZEA (0, 0.75 and 1 mg/kg) for 42 days. Initial and final body weight (BW), mean daily weight gain, mean daily feed intake, feed conversion and vulva volume were assessed at the time of blood sampling to determine ZEA and its metabolites in the serum. Blood samples were spun to obtain the serum, which was analyzed via HPLC-MS/MS. When the experimental period ceased, the animals were slaughtered and eviscerated in order to evaluate weight and length of the reproductive tract. The zootechnical performance was not affected by the presence of ZEA in the diet, and inclusion of AMA did not determine differences (P>0.05). ZEA caused a significant increase (P<0.05) in BW, length of the reproductive tract and vulva measurement (width, length and area), with no difference (P>0.05) between treatments with the addition of AMA to the diet (P>0.05). With respect to the evaluated metabolites, α-ZOL was detected above the limit of quantification in both unconjugated (>0.15 μg/kg) and unconjugated (>1.58 μg/kg) forms. The concentration of the remaining metabolites was below the limit of detection, thus confirming the results of the efficacy of AMA (P<0.05). The findings in this study contribute to the search of quality of the marketed AMA as well as to the assessment of analytical methods and biomarkers; these substances may represent an alternative to confirm the efficacy of such products in heifers and gilts.